BIOLOGICAL MANAGEMENT OF WILT OF BRINJAL - ARYA, SANJAY (Annals of Agricultural Research, 2014)
Biocontrol potential of Trichoderma viride, T. harzianum, T. longibrachiatum, T. pseudokoningi and Gliocladium virens was evaluated against wilt of brinjal (Fusarium oxysporum) under pot house conditions. All the biocontrol agents significantly improved germination percentage over inoculated control. Seed treatment with T. viride recorded the highest seed germination and soil incorporation of neem cakefurther improved its efficacy along with improvement in plant length and weight. This was followed by T. harzianum, T. longibrachiatum, T. pseudokoningi and G. virens.